Tired But Can’t Stop: Exploring the Association of Fear of Missing Out (FoMo) and Social Media Fatigue among Emerging Adults - Ardelia, Vania; Jaro'ah, Siti; Maghfiroh, Fitrania; Laksmiwati, Hermien (Indonesia Emerging Literacy Education, 2024)
Objective: Indonesia ranks third as the country with the most social media users, with emerging adults making up the largest group. On average, Indonesians spend almost 6 hours a day playing social media. This condition can cause both physical and psychological problems. One of the impacts of excessive social media use is Social Media Fatigue (SMF). The level of SMF is influenced by several factors, one of which is Fear of Missing Out (FoMo), which is a fear of missing out on experiences that others are enjoying. SMF and FoMo can significantly impact an individual's mental health. The link between the two conditions is clear, but there is little in-depth research linking the two. This study aimed to explore the association of Fear of Missing out (FoMo) with Social Media Fatigue (SMF) among emerging adults. Method: A cross-sectional study design was conducted among 157 men and women emerging adults. Participants completed a self-administered questionnaire that consisted of demographic characteristics, Fear of Missing Out scale, and Social Media Fatigue scale. Data were analyzed using descriptive analysis and Pearson Correlation statistic technique. Results: Descriptive analysis results showed that men showed a higher tendency of both fear of missing out and social media fatigue compared to women. Further, a significant yet moderate correlation was found between FoMo and SMF among emerging adults. Novelty: This study contributed to explore further on the relationship between fear of missing out (FoMo) and social media fatigue specifically among emerging adults.